Design and fabrication of drug‐delivery systems toward adjustable release profiles for personalized treatment. Issue 5 (16th May 2021) - Geraili, Armin; Xing, Malcolm; Mequanint, Kibret
Abstract: Advanced polymeric controlled delivery systems are designed to effectively treat chronic diseases by adjusting the temporal profile of drug release. Most conventional controlled‐release carriers provide a constant and sustained‐release profile of therapeutics for an extended time. Although these systems have improved the patients' compliance and adherence and have reduced the administration frequency, they cannot be used for optimal treatment of diseases that require variable patterns of drug release in the treatment regimen. These patterns and the specific rhythms of medical conditions determined by both the body's internal biological clock cycles (i.e., circadian rhythm) and each patient's characteristics call for patient‐specific controlled drug‐delivery systems that can provide adjustable drug release profiles. The importance of individualized therapy and the variety of biodegradable polymers with tunable physicochemical properties promote the design and manufacturing of polymeric delivery systems that release therapeutics at controllable rates. In the past two decades, novel biomaterials and fabrication methods have been utilized to improve the traditional drug‐delivery design and manufacturing technologies. This review article provides a critical discussion of emerging polymeric controlled‐release systems and the mechanisms through which they release their therapeutic agents. Advances and challenges in the design and the fabrication processes of polymeric drug‐delivery systems, particularly solid oral dosage forms and implantable microchips, with controllable release profiles of drugs, are reviewed, focusing on the application of microtechnology and 3D printing techniques in their manufacturing. Abstract : The specific rhythms of medical conditions determined by the body's internal biological clock cycles (i.e., circadian rhythm) and each patient's characteristics call for patient‐specific drug‐delivery systems that can provide adjustable drug release profiles. The importance of individualized therapy and the variety of biodegradable polymers with tunable physicochemical properties promote the design and manufacturing of polymeric delivery systems that release therapeutics at controllable rates. This review article provides a critical discussion of emerging controlled‐release systems and the mechanisms through which they release their therapeutic agents. Advances and challenges in the design and the fabrication processes of drug‐delivery systems, particularly solid oral dosage forms and implantable microchips, with controllable release profiles of drugs, are reviewed, focusing on the application of microtechnology and 3D printing techniques in their manufacturing.